Initial Public Offerings and Performance Evaluation: Evidence from the Indian Capital Market - Middi, Appala Raju (International Journal of Economics and Financial Issues, 2018)
This paper attempts to prove the existence of under-pricing of Indian Initial Public Offerings (IPOs). We examine the aftermarket performance for up to 12 months using a sample size of 25 IPOs issued in 2015. The sample reveals a 3% Raw Initial Returns on the first trading day close. Aftermarket performance is measured in terms of Market Adjusted Initial Returns for 30 days, 3 months and 12 months show an average of 6%, 17% and 26% respectively suggesting an over-performance of IPOs. Finally, using parameters employed in previous literature: firm age, market, proceeds, risk, and size, we conduct a regression analysis showing no factor affecting the under-pricing level. Keywords: Initial Public Offerings; Raw Initial Returns; Market Adjusted Initial Returns; Aftermarket JEL Classifications: F3, G2